THE EVOLUTION OF REALISM IN LATE NINETEENTH-CENTURY AMERICAN LITERATURE: SOCIAL CONTEXT AND LITERARY TRANSFORMATION - Iroda Egamberdiyeva Abdurahimovna; Najimov Dilshodbek Hasanboy o‘g‘li (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract This article explores the development of realism in late nineteenth-century American literature, focusing on its social, cultural, and historical foundations. The study examines how realism emerged as a reaction against romanticism and idealism, emphasizing objective representation of everyday life. Special attention is given to the works of Mark Twain and William Dean Howells, who played a crucial role in shaping the realist tradition. The research highlights how industrialization, urbanization, and changing social conditions influenced literary themes and narrative techniques. The findings demonstrate that realism not only reflected society but also contributed to the formation of American national identity and literary independence.